Nanopartículas para o tratamento do câncer cervical - Coury Ribeiro, Guilherme (Universidade Federal de São Carlos, 2026)
Cervical cancer represents a public health problem in Brazil, frequently characterized by diagnoses in advanced stages that compromise the clinical prognosis and raise the costs of the public healthcare system. Treatment for advanced carcinomas may involve the systemic administration of cisplatin, a chemotherapeutic agent with excellent pharmacological mechanics, whose therapeutic index is, however, limited by the occurrence of severe systemic side effects and the development of tumor resistance. Faced with this scenario, nanomedicine has studied ways to optimize drug targeting specifically to the tumor microenvironment. This work introduces the concepts of nanomedicine and presents a comparative analysis of three nanoplatforms documented in the scientific literature for the delivery of cisplatin in HeLa cervical carcinoma cell lines. The studied works involve estrone-targeted PEGylated liposomes, polymeric PLGA nanoparticles in a co-delivery regimen, and mesoporous silica nanoparticles functionalized with carboxylic groups. The results revealed that the chemical nature of each matrix outlines distinct biological and physicochemical profiles. ES-SSL-DDP liposomes showed the highest in vitro cytotoxic potency, increasing efficacy by 169.6-fold compared to the free drug, driven by active targeting of estrone via estrogen receptors in HeLa cells. In turn, MSNs-C demonstrated quantitative superiority in loading parameters, with an approximate encapsulation efficiency of 63.7% and a loading capacity of 11.3%. In addition, they exhibited highly responsive release at more acidic pH, ensuring drug protection under neutral physiological conditions. PLGA nanoparticles enabled a synergistic therapeutic effect in inducing apoptosis when combined with silibinin, although they lack direct cellular uptake data. Regarding colloidal stability, the PLGA polymeric nanoparticle exhibited the highest negative zeta potential module of -59 mV. In summary, the analyzed nanocarriers demonstrate remarkable potential to overcome the limitations of classical chemotherapy.
Nanoparticles for the treatment of cervical cancer
Keywords: Câncer cervical; Cisplatina; Nanopartícula; PLGA; Sílica mesoporosa; Lipossoma; CIENCIAS EXATAS E DA TERRA::QUIMICA; 3. Saúde e Bem-Estar